2019
DOI: 10.3390/jcm8081256
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sclerosis Serum Steers the Differentiation of Adipose-Derived Stem Cells Toward Profibrotic Myofibroblasts: Pathophysiologic Implications

Abstract: Systemic sclerosis (SSc; scleroderma) is characterized by life-threatening progressive multiorgan fibrosis orchestrated by profibrotic myofibroblasts originating from different sources. Because recent data demonstrated that the majority of myofibroblasts in a murine scleroderma model arise from adipocytic progenitors through the adipocyte-myofibroblast transition process, we sought to determine whether the SSc microenvironment may affect the differentiation potential of adipose-derived stem cells (ADSC). Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
7
1
Order By: Relevance
“…These results appear to contrast with recent studies of miRs in silico, which reported a pro-fibrotic ASC signature from SSC patients [23]. Sera from SSc patients have also been shown to favor differentiation of healthy ASC into profibrotic myofibroblast-like cells in vitro [43].…”
Section: Discussioncontrasting
confidence: 90%
“…These results appear to contrast with recent studies of miRs in silico, which reported a pro-fibrotic ASC signature from SSC patients [23]. Sera from SSc patients have also been shown to favor differentiation of healthy ASC into profibrotic myofibroblast-like cells in vitro [43].…”
Section: Discussioncontrasting
confidence: 90%
“…By contrast, ASCs represent a more homogeneous population of cells and early phase clinical trials reported beneficial effects of autologous ASC transplantation in the alleviation of cutaneous symptoms in SSc patients [23][24][25]. However, there is still controversy over the use of autologous or allogeneic ASCs in the clinic because there are studies suggesting functional alterations of these cells in SSc [26,27]. Therefore, with the view of the potential therapeutic application of autologous ASCs in mind, we have performed a basic characterization of these cells and compared the phenotype and secretory potential of RD patients' ASCs (RD/ASCs) with the corresponding features of ASC lines originating from healthy donors (HDs).…”
Section: Introductionmentioning
confidence: 99%
“…In perspective, we frankly acknowledge that our data represent the necessary groundwork for further investigation aimed at unveiling the likely multiple factors that, in SSc, may prevent a timely lymphangiogenic response to the ongoing destruction of the dermal microlymphatic network [9][10][11][12]. In this regard, it is noteworthy that several factors with proven anti-lymphangiogenic activity, such as transforming growth factor-β1, thrombospondin, and endostatin, are known to be increased and to have pathogenic implications in SSc [1,6,14,23,29,[44][45][46][47][48]. In such a context, a very recent study has demonstrated that levels of CXCL10 and CXCL11, two C-X-C chemokines exerting angiostatic effects through their receptor CXCR3-B [49], are strongly increased in the circulation of SSc patients from the earliest disease stages, and may represent good biomarkers of vascular damage progression [50].…”
Section: Discussionmentioning
confidence: 78%